Peningkatan Kemampuan Dasar Bahasa Inggris melalui Penguatan Kosakata dan Pelafalan Sederhana Terhadap Siswa Thailand - Halimatus Sya'diyah; Hikmal Hasan; Faiz Azizi; Fahrur Roji; Imroatus Sholiha (Jurnal Pengabdian kepada Masyarakat Desa (JPMD), 2025)
The limited English proficiency of students at Darul Muhmin Elementary School in Thailand constitutes a major challenge encountered during a three-month community service program conducted by Indonesian university students. The students experienced difficulties in understanding basic vocabulary, simple sentence structures, and were not accustomed to using English in their daily lives. This condition was influenced by limited exposure to English and the lack of varied instructional methods. This community service activity aimed to foster students’ interest in learning English, provide an enjoyable learning experience, and improve their mastery of vocabulary and pronunciation. The method employed in this program was a qualitative descriptive approach using Communicative Language Teaching. The implementation of the program was carried out through three stages: planning, implementation, and evaluation. The instructional strategies included vocabulary reinforcement, the introduction of basic grammar, and the habituation of daily conversation adjusted to the students’ proficiency levels. Learning media utilized in this program consisted of printed images, educational songs, whiteboards, and simple technological tools such as mobile phones and Bluetooth speakers. Evaluation was conducted through direct observation of students’ participation, responses, and their ability to comprehend and use basic English vocabulary. The results indicated an increase in students’ learning enthusiasm, improved basic English comprehension, and enhanced self-confidence in using English. This activity demonstrates that simple teaching methods combined with a communicative and enjoyable approach can effectively enhance basic English proficiency among elementary school students in Thailand with limited access to English learning.